Effect of Organic Loading Rate on Hydrogen (H2) and Methane (CH4) Production in Two-stage Fermentation under Thermophilic Conditions using Palm Oil Mill Effluent (POME) - Santhana, Krishnan; Singh, Lakhveer; Mimi Sakinah, A. M.; Thakur, Sveta; Zularisam, A. W.; Johan, Sohaili (Elsevier, 2016)
The present study dealt with hydrogen and methane production in a sequential up-flow anaerobic sludge blanket (UASB) and continuous stirred tank reactor (CSTR) at thermophilic temperature. The POME was used as a suitable substrate of carbon source. The effect of various OLR was investigated from 25 kg-COD/m3·d to 125 kg-COD/m3·d at a constant hydraulic retention time (HRT) of 6 h. The UASB-H2 reactor was operated successfully at the OLR of 75 kg-COD/m3·d when the proportion of H2 in biogas, volumetric production rate of H2, specific hydrogen production rate (SHPR) and H2 yield reached the maximum values of 35%, 2.1 l/d, 175.15 ml H2/g MLVSS-d and 49.22 ml H2/g CODapplied respectively. Further, the effluent from the UASB was directly fed into the CSTR at various OLR ranging from 4 kg-COD/m3·d to 20 kg-COD/m3·d for CH4 production. The maximum CH4 content, volumetric production rate of CH4, specific methane production rate (SMPR) and CH4 yield obtained were 65%, 13 l/d, 325.13 ml CH4/g MLVSS-d, and 155.87 ml CH4/g CODapplied respectively. The effluent from CH4 reactor was recycled at feed flow rate recycle ratio of 1:1 to UASB unit and pH was maintained at 5.5, subsequently resulted in COD removal of 85%.